Langerhans cell histiocytosis - Victor V. Fomin; Maria I. Mitkina; Elena N. Popova; Liubov A. Ponomareva; Alina A. Chinova (LLC "MEDIAFORMAT", 2023)
Langerhans cell histiocytosis is a rare proliferative disease of histiocyte-like cells, the peak incidence of which occurs in early childhood. Pulmonary Langerhans Cell Histiocytosis is one of the forms of this disease, but it usually affects young smokers aged 30-40 years. Smoking cessation is the most important recommendation for such patients. The article contains several clinical cases and a literature review.